A Juridical Analysis of the Caning Implementation in Aceh Prisons and its Relations to Islamic Laws - Syarif, Muhammad; Abbas, Syahrizal; Rahmadon, Rahmadon; Musfira, Musfira (Universitas Islam Sultan Agung, 2022)
The Aceh government has implemented Islamic Sharia regulations by enacting Qanun Aceh Number 7 of 2013 concerning Jinayat Procedural Law, and Article 262 contains provisions regarding the implementation of flogging in public places. However, according to Article 30 Paragraph (3) of the Aceh Governor Regulation Number 5 of 2018 concerning the Implementation of Jinayah Procedural Law, the execution of flogging is restricted to prisons and detention centers. This study aims to outline the legal arguments for shifting the implementation of flogging in Aceh and the Islamic legal provisions related to carrying out flogging in public places. This research uses a normative legal method with a statute approach that refers to the concept of law as a rule and also uses Islamic legal doctrine, which is then analyzed qualitatively and described descriptively to find the alignment between the core issues and the normative provisions. The results of the research show that the main reason for issuing the Governor's Regulation regarding the implementation of flogging in prisons is to increase investment, as the implementation of flogging in Aceh has faced opposition from external parties. However, the issuance of the Governor's Regulation contradicts the system of forming legislation in Indonesia and legally lacks legal force. According to Islamic law provisions, the execution of flogging must be witnessed by a group of believers, as explained in the Quran, Surah An-Nur, verse 2. The implementation of flogging in prisons cannot be witnessed, whereas this is an integral part of the agreed implementation of flogging. There needs to be a specific and easily accessible location for the public as a place to carry out flogging penalties.